Fan-athlete interaction and Twitter tweeting through the giro : a case study - Kassing, Jeffrey W.; Sanderson, Jimmy (London : Human Kinetics, Inc., 2010)
This case study examines how fans can experience a major sporting event (cycling's Tour of Italy) through a particular new communication technology platform--Twitter. To explore this possibility the authors tracked the "tweets" sent out by a selection of American and English-speaking riders during the 3-week race. Their analysis of these texts revealed that Twitter served to increase immediacy between athletes and fans. This occurred as athletes provided commentary and opinions, fostered interactivity, and cultivated insider perspectives for fans. These activities position Twitter as a powerful communication technology that affords a more social vs. parasocial relationship between athletes and fans.
Originally published in Kassing, J. W., & Sanderson, J. (2010). Fan-athlete interaction and Twitter tweeting through the Giro: A case study. International Journal of Sport Communication, 3(1), 113-128. DOI:.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Twitter (Firm) -- Case studies; Communication in sports -- Case studies; Sports spectators -- Case studies